Uranyl(II) and Thorium(IV) Complexes of N-(o-Hydroxy Substituted Benzyl) Alanines - Ballabh Karnatak, Kanti; Pandey, Hema; Sharma, Reeta; Mohan Mehrotra, Radha; Chandra, Madhup (Asian Journal of Chemistry, 2010)
Several uranyl(II) and thorium(IV) complexes of N-(o-hydroxy substitued benzyl) alanines have been isolated from 50% (v/v) aqueous-DMSO medium in 1 : 1 and 1 : 2 molar ratios which were characterized by elemental analysis and spectral measurements.